The Cambridge companion to Augustine - Meconi, David Vincent (Cambridge companions to philosophy, 2014)
It has been over a decade since the first edition of The Cambridge Companion to Augustine was published. In that time, reflection on Augustine's life and labors has continued to bear much fruit: significant new studies into major aspects of his thinking have appeared, as well as studies of his life and times and new translations of his work. This new edition of the Companion, which replaces the earlier volume, has eleven new chapters, revised versions of others, and a comprehensive updated bibliography. It will furnish students and scholars of Augustine with a rich resource on a philosopher whose work continues to inspire discussion and debate.